Mechanics of Biological Systems and Materials, Volume 6 Proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics - Korach, Chad S.; Tekalur, Srinivasan Arjun; Zavattieri, Pablo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Mechanics of Biological Systems and Materials, Volume 6 of the Proceedings of the 2016 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the sixth volume of ten from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: Soft Material Mechanics Bio-Engineering and Biomechanics Cells Mechanics Biomaterials and Mechanics Across Multiple Scales Biomechanics Biotechnologies Traumatic Brain Injury Mechanics.
1 Mechanic Adaptability of Metastatic Cells in Colon Cancer -- 2 Nano mechanical Response of Red Blood Cells -- 3 Scale Dependence of the Mechanical Properties of Interfaces in Crustaceans Thin Films -- 4 Dynamic Analysis of Human Knee -- 5 Viscohyperelastic Calibration in Mechanical Characterization of Soft Matter -- 6 Contact Zone Evaluation of Dental Implants Using Digital Photoelasticity -- 7 Evolution of the Skin Microstructural Organization During a Mechanical Assay -- 8 A Numerical Study of a Biaxial Sollicitation to Set up the Displacement Field Measurement of ex Vivo Mouse Skin -- 9 Dynamic Polarization Microscopy for In Situ Measurements of Collagen Fiber Realignment During Impact -- 10 Self shifting Neutral Axis in Hierarchical Structured Natural Composites Bamboo -- 11 High speed Holography for In vivo Measurement of Acoustically Induced Motions of Mammalian Tympanic Membrane -- 12 Rheology of Soft and Rigid Micro Particles in Curved Microfluidic Channels -- 13 Microfluidic Approaches for Biomechanics of Red Blood Cells -- 14 Custom Indentation System for Mechanical Characterization of Soft Matter -- 15 Experimental Evaluation of Blast Loadings on the Ear and Head With and Without Hearing Protection Devices -- 16 A Mechano-Hydraulic Model of Intracranial Pressure Dynamics -- 17 Regional Variations in the Mechanical Strains of the Human Optic Nerve Head -- 18 Experimental Electromechanics of Red Blood Cells Using Dielectrophoresis-based Microfluidics -- 19 Microbuckling of Fibrous Matrices Enables Long Range Cell Mechanosensing -- 20 The Growth and Mechanical Properties of Abalone Nacre Mesolayer -- 21 Evaluation of Precise Optimal Cyclic Strain for Tenogenic Differentiation of MSCs -- 22 Effect of architecture on cell functions of electrospun fiber membrane -- 23 Controlling hESC-CM Cell Morphology on Patterned Substrates Over a Range of Stiffness -- 24 Cytoskeletal Perturbing Drugs and Their Effect on Cell Elasticity.
Keywords: Mechanics, Applied; Biomaterials; Orthopedics; Biotechnology; Biomedical engineering; Engineering Mechanics; Biomaterials; Orthopaedics; Biotechnology; Biomedical Engineering and Bioengineering